Analisis Waktu Pelaksanaan Proyek Konstruksi dengan Variasi Penambahan Jam Kerja - Priyo, Mandiyo; Sartika, Sartika (Universitas Muhammadiyah Yogyakarta, 2014)
Time and cost greatly affect the success and failure of a project. Measure of the success of a project is usually seen short turnaround time at minimal cost without leaving the quality of result. Systematic project management is required to ensure the project implementation time in accordance with the contract or even faster that the cost could provide benefits. And also avoid any penalties due to delays in project completion. Purpose of this study is to calculate the change of cost and time of implementation project with variations additional hours of 1 hour to 4 hours of overtime by using microsoft project programs. And to compare the results between the cost of fines with changes in costs before and after the addition of working hours (overtime). The results of this study have shown that (1) The minimum project cost was obtained at the time of normal conditions without the addition of overtime hours Rp 25,923,636,641.50 while for the minimum time the project was obtained on the addition of 4 hours is 197.84 days of normal duration of 217 days with the addition of cost of Rp 215,838,008.94 from the normal total cost of Rp. 25,923,636,641.50 to Rp 26,139,474,650.44 (2) Additional hours worked best option is additional three hours of work, in this condition the costs Rp 139,469,427.19 with profits generated Rp 327 156 .032,35.